Evaluation Of The Multitarget Potential Of Phytocannabinoid Fractions Against Alzheimer’s Disease - Musso, Florencia Antonella (2025)
Alzheimer’s disease (AD) is a multifactorial neurodegen- erative disorder for which current therapies are mainly symptomatic. Thus, the search for multitarget agents re- mains a major challenge. Cannabis sativa represents a promising source of bioactive metabolites with neuropro- tective potential. In this study, an ethanolic extract of C. sativa inflorescences was screened for acetylcholinesterase (AChE) inhibitory activity through a bioassay-guided fractionation approach, leading to the identification of subfractions enriched in the phytocannabinoid acids (PCa) tetrahy- drocannabinolic acid (THCA) and cannabidiolic acid (CBDA). The subfraction with the highest THCA content exhibited the strongest enzymatic inhibition. This prompted us to evaluate THCA in a dose-response assay on endocannabinoid 2-arachidonoylglycerol (2-AG) hydro- lysis in an experimental model of synaptic amyloidosis induced by β-amyloid oligomers, as occurs in AD. At 30 μM, THCA reduced monoacylglycerol lipase (MAGL) ac- tivity, the main enzyme responsible for 2-AG degrada- tion, thereby potentially increasing the availability of this neuroprotective endocannabinoid, previously reported to be reduced in AD. Further enzymatic assays demonstrated that THCA, CBDA, as well as the 1:1 and 1:5 THCA:CBDA subfractions inhibited MAGL activity, while CBDA and 6:1 THCA:CBDA subfraction stimulated diacylglycerol lipase (DAGL), a key enzyme for 2-AG biosynthesis. Together, these results suggest a dual mechanism exerted by PCa, enhancing cholinergic neurotransmission (via AChE inhibition) and restoring 2-AG levels (via MAGL or DAGL modulation), potentially contributing to synaptic function. Our results emphasize the therapeutic potential of PCa as multitarget modulators in AD. Future in vivo studies will be essential to validate efficacy and safety, consolidating their role as candidates for AD treatment.